Heart Failure Associated with Lymphoid Histiocytosis with Extramedullary Erythropoiesis in the Spleen: Case Report - de Sousa Silva, Samuel (Pubvet, 2018)
The present report relates to heart failure and systemic inflammatory changes when describing a clinical case of a male canine patient with heart failure and lymphoid histiocytosis with extramedullary erythropoiesis in the spleen. The patient presented a generalized increase of cardiac chambers with dysfunction in both ventricles and enlarged spleen with presence of nodules spread throughout the parenchyma. Splenectomy was performed by biopsy of this spleen, arriving at the diagnosis by cytology. Heart failure causes systemic inflammatory changes, this correlation with pathologies related to persistent immune stimulation has not yet been studied. Surgery performed and continued treatment for heart failure restored the animal’s health.